State-of-the-Art Report on Fiber-Reinforced Lightweight Aggregate Concrete Masonry - Saul Rico; Roshanak Farshidpour; Fariborz M. Tehrani (Advances in Civil Engineering)
Masonry construction is the most widely used building method in the world. Concrete masonry is relatively low in cost due to the vast availability of aggregates used within the production process. These aggregate materials are not always reliable for structural use. One of the principal issues associated with masonry is the brittleness of the unit. When subject to seismic loads, the brittleness of the masonry magnifies. In regions with high seismic activity and unspecified building codes or standards, masonry housing has developed into a death trap for countless individuals. A common approach concerning the issue associated with the brittle characteristic of masonry is addition of steel reinforcement. However, this can be expensive, highly dependent on skillfulness of labor, and particularly dependent on the quality of available steel. A proposed solution presented in this investigation consists of introducing steel fibers to the lightweight aggregate concrete masonry mix. Previous investigations in the field of lightweight aggregate fiber-reinforced concrete have shown an increase in flexural strength, toughness, and ductility. The outcome of this research project provides invaluable data for the production of a ductile masonry unit capable of withstanding seismic loads for prolonged periods.